Seminar Kewirausahaan – Identifikasi Keinginan atau Kebutuhan Bagi Persekutuan Pemuda Gereja Toraja (PPGT) Klasis Nonongan Salu - Rahma Gusmawati Tammu; Marniati Marniati; Mey Enggane Limbongan; Dina Ramba'; Helba Rundupadang (Fakultas Teknik Universitas Cenderawasih, 2023)
The Toraja Church Youth Fellowship (PPGT) is an inseparable part of the church's organizational structure. PPGT has various work programs designed to foster enthusiasm and direct the young generation to become an independent generation in various aspects. Entrepreneurship seminar activities in the Sub Theme: Identifying Wants or Needs aim to provide financial education for the younger generation so they are able to manage personal finances through self-identification of whether they buy goods because they really need them or just because they want them. This activity is attended by more than ± 25 people. The method used is lecture, discussion and question and answer. The result of this community service activity is that the young generation is able to define what wants and needs are and is able to identify needs or desires in making decisions to purchase a product.